Mechatronic components : roadmap to design - Kececi, Emin Faruk (Butterworth-Heinemann, 2019)
Mechatronic Components: Roadmap to Design explains the practical application of mechatronics, including sections on adaptive structures, robotics and other areas where mechanics and electronics converge. Professional engineers in a variety of areas will find this textbook to be extremely helpful with its in-depth use of flow diagrams and schemes that help readers understand the logic behind the design of such systems. Using approximately 130 different components with diagrams and flowcharts that help engineers from different fields understand the general properties and selection criteria of a component, this book presents a comprehensive resource on mechatronic components.